Post-treatment of secondary wastewater treatment plant effluent using a two-stage fluidized bed bioreactor system - Safari, Golam Hossein; Yetilmezsoy, Kaan; Mahvi, Amir Hossein; Zarrabi, Mansur (BMC, 2013)
The aim of this study was to investigate the performance of a two-stage fluidized bed reactor (FBR) system for the post-treatment of secondary wastewater treatment plant effluents (Shahrak Gharb, Tehran, Iran). The proposed treatment scheme was evaluated using pilot-scale reactors (106-L of capacity) filled with PVC as the fluidized bed (first stage) and gravel for the filtration purpose (second stage). Aluminum sulfate (30 mg/L) and chlorine (1 mg/L) were used for the coagulation and disinfection of the effluent, respectively. To monitor the performance of the FBR system, variation of several parameters (biochemical oxygen demand (BOD5), chemical oxygen demand (COD), turbidity, total phosphorous, total coliform and fecal coliform) were monitored in the effluent wastewater samples. The results showed that the proposed system could effectively reduce BOD5 and COD below 1.95 and 4.06 mg/L, respectively. Turbidity of the effluent could be achieved below 0.75 NTU, which was lower than those reported for the disinfection purpose. The total phosphorus was reduced to 0.52 mg/L, which was near the present phosphorous standard for the prevention of eutrophication process. Depending on both microorganism concentration and applied surface loading rates (5-10 m/h), about 35 to 75% and 67 to 97% of coliform were removed without and with the chlorine addition, respectively. Findings of this study clearly confirmed the efficiency of the FBR system for the post-treatment of the secondary wastewater treatment plant effluents without any solid problem during the chlorination.
Keywords: Secondary effluent; COD; Coliform; Fluidized bed reactor; PHOTOCATALYTIC DISINFECTION; ANAEROBIC TREATMENT; REACTOR; SOLAR; INACTIVATION; FILTRATION; PHOSPHATE; BACTERIA; REMOVAL; FILTER; Engineering; Environmental Sciences & Ecology